Digital principles and design - Givone, Donald D. (McGraw-Hill, 2003)
With thw strong impact of digital technology on our everyday lives, it is not surprising that a course in digital concepts and design is a standard requirement for majors in computer engineering, computer science, and electrical engineering. An introductory course is frequently enountered in the first or second year of their undergraduate programs. Additional courses are then provided to refine and extend the basic concepts of the introductory course. This book is suitable for an introductory course in digital principles with emphasis on logic design as well as for a more advance course. With the exception of the appendix, it assumes no background on the part of the reader. The intent of the author not to just present a set of procedures commonly encountered in digital design but, rather, to provide justifications underlying such procedures. Since no background is assumed, the book can be used by students in computer engineering, computer science, and electrical engineering.